2018
DOI: 10.1021/acs.jpcc.8b06778
|View full text |Cite
|
Sign up to set email alerts
|

Boosting the Temperature Detection Accuracy of Luminescent Ratiometric Thermometry via a Multifunction Fit Strategy

Abstract: The influence of fit strategy on the temperature detection accuracy of luminescence ratiometric thermometry is investigated here. In the range of 303–783 K, the typical 2H11/2/4S3/2–4I15/2 upconversion emission lines of Er3+ embedded in calcium tungstate are investigated as a function of temperature. It is found that using the conventional one-function fit method over the whole temperature range leads to a mean error of 3.47 K. By contrast, the strategy, namely, dividing the whole board temperature range into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…[163][164][165] Besides, U 1 and U 2 intensities are derived from the accumulation of two UCL emissions centered at respective wavelengths, 44,69,87 such as "U 520+527nm ↑/U 540+547nm ↓". 69 Previous studies on ratiometric UCL nanoprobes probably do not provide peak wavelengths of U 1 and U 2 but indicate the related electron transitions, 31,37,38,44,60,66,69,75,80 UCL visible color changes, 39,53,93,97,98,141,161 the respective excitation wavelengths, [108][109][110]130 or the intervals of emission bands, 80,92 such as…”
Section: Ratiometric Dual-signal Modes Of Ratiometric Ucl Nanoprobesmentioning
confidence: 99%
See 4 more Smart Citations
“…[163][164][165] Besides, U 1 and U 2 intensities are derived from the accumulation of two UCL emissions centered at respective wavelengths, 44,69,87 such as "U 520+527nm ↑/U 540+547nm ↓". 69 Previous studies on ratiometric UCL nanoprobes probably do not provide peak wavelengths of U 1 and U 2 but indicate the related electron transitions, 31,37,38,44,60,66,69,75,80 UCL visible color changes, 39,53,93,97,98,141,161 the respective excitation wavelengths, [108][109][110]130 or the intervals of emission bands, 80,92 such as…”
Section: Ratiometric Dual-signal Modes Of Ratiometric Ucl Nanoprobesmentioning
confidence: 99%
“…As summarized in Table 1, previous studies have largely reported various types of ratiometric UCL nanoprobes for temperature sensing. [168][169][170][171][172][173][174][175][176]193,194 Most of the nanoprobe systems consist of lanthanide-doped UCNPs, other upconverting luminescent inorganic materials, 29,36,40,43,45,47,48,54,[56][57][58][59][60][61]65,[73][74][75][76] and the derivatives with functional modifications, including the core@shell, 37,38,41,68,72,78,79 hollow/porous, 38 complexes, 46,49,51 hybrid, 32,52 mixture, 33,35 assembly, 34,55 or engineering structures.…”
Section: Sensing Of Temperaturementioning
confidence: 99%
See 3 more Smart Citations